Severe acute pancreatitis due to tamoxifen-induced hypertriglyceridemia with diabetes mellitus - Kim, Young Ae; Lee, Sol; Jung, Ji Woong; Kwon, Yu Jin; Lee, Gyeong Bok; Shin, Dong Gue; Park, Sang Su; Yun, Jin; Jang, Yong-Seog; Cho, Dong Hui (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
The side effects of tamoxifen are generally mild, including the effect on lipoprotein metabolism. However, there are few cases of severe tamoxifen induced hypertriglyceridemia. Hypertriglyceridemia is a marked risk factor for acute pancreatitis and approximately 2% to 5% of cases of acute pancreatitis are related to drugs. We report on tamoxifen-induced hypertriglyceridemia and acute pancreatitis in a 40 years old woman with type 2 diabetes mellitus occurred by dexamethasone. She was treated with insulin infusion and fenofibrate, and goserelin acetate was started instead of tamoxifen after discharge from the hospital. Also, probable pathogenic hypotheses about the correlation between tamoxifen and dexamethasone induced type 2 diabetes mellitus on severe acute pancreatitis are provided. Clinicians should take care of risks of severe acute pancreatitis on using tamoxifen, especially for patients with dexamethasone induced diabetes mellitus. These individuals should undergo pre-post tamoxifen lipid screening and careful history taking of drugs, including dexamethasone.